Analisis Penerapan Ice Breaking Dalam Pembelajaran Kurikulum Merdeka Peserta Didik Di Sekolah Dasar - Vivi Eka Erviana; Didik Tri Setiyoko; Moh. Toharudin (Concept: Journal of Social Humanities and Education, 2023)
The main problem in this study is how to apply ice breaking in the learning of fifth grade students at SD Negeri Pesantunan 05, the effect of ice breaking in increasing student learning concentration and the advantages and disadvantages of ice breaking in learning. This type of research is descriptive-qualitative. Data collection techniques used are observation, interviews and documentation. The analytical method used is collecting data, data reduction, data presentation and verification. The results of this study indicate that the application of ice breaking in student learning in elementary schools can have an effect on increasing student learning concentration as long as the learning process is going well. The types of ice breaking that are often used by teachers are singing, songs and clapping which are carried out at the end of learning or on the sidelines of learning. With the application of Ice Breaking in learning can make students more active, enthusiastic about learning, and concentrating in the learning process takes place, in the application of Ice Breaking the teacher of course looks at the conditions and atmosphere of the class first whether it is possible to carry out Ice Breaking activities. We often encounter weaknesses and strengths during the process of implementing Ice breaking in mathematics learning. The advantages of implementing Ice breaking can shorten the time during the learning process, making the class atmosphere fun and cheerful. The drawback is the teacher's lack of creativity in implementing the types of ice breaking that are carried out in the classroom.